2014
DOI: 10.4081/rt.2014.5355
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cystic Schwannoma in the Neck Masquerading as Branchial Cleft Cyst

Abstract: One-third of schwannomas occur in head and neck region, mostly in the parapharyngeal region. Cystic change is seen in only 4% of schwannomas. The diagnosis of such tumors remains a challenge due to the rarity of these lesions and limited utility of fine needle aspiration cytology. When cystic, branchial cleft cyst is an important differential diagnosis more so due to radiological resemblance. We present a case of 42-year-old male with left sided neck mass masquerading as branchial cleft cyst clinically and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
(17 reference statements)
0
9
0
3
Order By: Relevance
“…Of all extracranial schwannomas, head and neck region accounts for 25– 45% of the cases whereas intraoral schwannomas are extremely rare and account for only 1% of cases. [ 2 ] Intraoral schwannomas most commonly affect the tongue, followed by palate, buccal mucosa, lip, and gingiva. [ 3 ] Schwannomas affecting the tongue arise from the hypoglossal nerve and vagus nerve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all extracranial schwannomas, head and neck region accounts for 25– 45% of the cases whereas intraoral schwannomas are extremely rare and account for only 1% of cases. [ 2 ] Intraoral schwannomas most commonly affect the tongue, followed by palate, buccal mucosa, lip, and gingiva. [ 3 ] Schwannomas affecting the tongue arise from the hypoglossal nerve and vagus nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Mucinous degeneration, necrosis, hemorrhage, and microcysts formation are thought to be the reasons for these cystic changes. [ 2 ] FNAC in such cases may yield hypocellular fluid altogether missing the solid cellular areas. The aspirated fluid may contain individual spindle cells, fibroblasts, histiocytes, or lymphocytes but in the absence of characteristic cellular architecture, such schwannomas may escape diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that when lateral cervical cystic lesion is encountered a differential diagnosis of neurogenic neoplasm with cystic changes should be included. Bohara S et al 16 reported a case with left neck mass masquerading as branchial cleft cyst clinically and radiologically; however histopathological examination showed it to be schwannoma.…”
Section: Discussionmentioning
confidence: 99%
“…The cystic variants comprise of 4% tumours. [1,4,5] The cystic Schwannoma grows more rapidly than non-cystic type.…”
Section: Introductionmentioning
confidence: 99%